Characterization of shallow groundwater in Eocene sediments of Panama Canal Watershed using electrical techniques - Díaz, Irving (Universidad Tecnológica de Panamá, Panamá, 2012)
This work is focused on the detection of seepages caused by the affluent located in a small area of the Panama Canal Basin during the dry season, and to define the subsurface stratigraphy (Eocene sediments) that characterize this area through a geophysical survey. Two electrical resistivity tomography were developed to identify the extent of infiltration and the nature of the clay layers vertically and laterally, these results were corroborated by a drilling operation in the vicinity of electrical tests and based on this information, established a model for a two-dimensional geoelectric profile in order to compare (i) the pseudo-sections of synthetic and measured apparent electrical resistivity, and (ii) the electrical resistivity tomography as a result of the inversions of such pseudo-sections. The results of electrical resistivity tomography obtained in the two profiles revealed the existence of (i) a surface layer moderately resistant (18-85 ohm.m) with a thickness not exceeding 1,8 m, (ii) an area of high electrical conductivity (3,8 to 10,7 ohm.m) with a thickness not exceeding 9.5 m and (iii) a resistant substratum with electrical resistivity values calculated in excess of 30,1 ohm.m and a range depth ranging from 2 to 11,5 m. The drilling operation in the vicinity of the geophysical tests revealed the presence of clay with varying moisture content and density, and thicknesses that corroborate the results of the geophysical evidence. The two-dimensional geoelectrical model of Profile 1 was established according to the results of electrical resistivity tomography as well as the profile and information of the drilling operation. Based on the results of this study, we conclude that the infiltrations generated by the affluent in this part of the Isthmus of Panama are very important, even in periods when precipitation levels are.